Self-help assessment and training support system for special children [electronic resource] - Milton Wider, 1988-, author; Abd. Hamid Ahmad, supervisor; Fakulti Kejuruteraan Elektrik (2011)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Elektronik Perubatan)) - Universiti Teknologi Malaysia, 2011